2005
DOI: 10.1038/nsmb916
|View full text |Cite
|
Sign up to set email alerts
|

Insights into hRPA32 C-terminal domain–mediated assembly of the simian virus 40 replisome

Abstract: Simian virus 40 (SV40) provides a model system for the study of eukaryotic DNA replication, in which the viral protein, large T antigen (Tag), marshals human proteins to replicate the viral minichromosome. SV40 replication requires interaction of Tag with the host single-stranded DNA-binding protein, replication protein A (hRPA). The C-terminal domain of the hRPA32 subunit (RPA32C) facilitates initiation of replication, but whether it interacts with Tag is not known. Affinity chromatography and NMR revealed ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(133 citation statements)
references
References 51 publications
6
116
0
Order By: Relevance
“…Structural studies have indicated that the C terminus of RPA2 makes direct contacts with similar motifs in the repair and recombination factors XPA, UNG2, and Rad52 (50). SV40 large T antigen also interacts with this domain but through a different motif (51). Strikingly, interactions between aRPA and these different protein partners vary considerably.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies have indicated that the C terminus of RPA2 makes direct contacts with similar motifs in the repair and recombination factors XPA, UNG2, and Rad52 (50). SV40 large T antigen also interacts with this domain but through a different motif (51). Strikingly, interactions between aRPA and these different protein partners vary considerably.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most critical primase interactions is with ssDNA templates coated with replication protein A (RPA). RPA is a modular protein, and its ability to directly interact with many different proteins facilitates assembly and progression of DNA processing machinery (19,20). For the simian virus 40 (SV40) model system, interactions of pol-prim with RPA and the SV40 large T-antigen (Tag) helicase are required for efficient initiation of replication on the SV40 genome (21,22).…”
mentioning
confidence: 99%
“…Understanding the timed formation and significance of protein-protein interactions during the different steps of the initiation reaction remains an active field of research [22,29]. The peptides with their marked specificities should be helpful in future studies to delineate more precisely the importance of mutual interactions between RPA, Tag and Pol in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction sites of different strengths have been mapped to DBD-A and N-terminal sequences of p70 and to a winged helix-loop-helix motif in the C-terminus of p32 [18,21,22].…”
Section: Introductionmentioning
confidence: 99%